Transformational Leadership of Kiai in Character Building: Exploring Teachers' Lived Experience in Islamic Institutions - Mawardi Mawardi; Aan Komariah; Sururi Sururi; Suryadi Suryadi; Eka Prihatin; Mawardi Mawardi; Aan Komariah; Sururi Sururi; Suryadi Suryadi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This research explores the lived experience of teachers implementing Islamic leadership values in educational institutions through an interpretative phenomenological analysis approach. Involving one teacher participant from an Islamic secondary school undergoing management reform, this study identifies significant gaps between ideal Islamic leadership and practical implementation. Three major themes emerged: an Islamic value-practice gap, in which Islamic principles were formally invoked in institutional discourse yet incompletely operationalized in relational and decision-making structures; a capacity-readiness deficit, in which structural reform was introduced ahead of human resource preparation, producing implementation failure that was rational rather than attitudinal in character; and professional development formalism, in which institutional learning programs were experienced as certification-oriented compliance exercises rather than substantive supports for teacher professional identity. Together, these themes converge on a central finding: theological commitment at the leadership level does not, by itself, produce Islamic value enactment at the organizational level. The study contributes theoretical insights for contextualizing Islamic leadership in modern educational organizations and provides practical recommendations for improving institutional management through participatory governance mechanisms, sequenced capacity building, and professionally relevant learning programs.